Kontrastivno o jezikoslovnih spolnih kategorijah - slovenska in italijanska osebna občna imena za javne funkcije - Grošelj, Robert (Slavistična revija, 2019)
The article analyzes linguistic gender categories in Slovene and Italian, with special emphasis on personal nouns denoting selected public offices (e.g., Slovene minister, ministrica; Italian il ministro, la ministra). Both languages have grammatically and lexically feminine and masculine personal nouns; the referential gender of masculine nouns is wider, as they can refer to male and male and/or female referents, and in Italian, also exclusively to female referents. Agreement is controlled mainly by grammatical (and corresponding lexical) gender; referential gender can trigger agreement in the case of gender exclusive categories, as seen in the names for public positions in Italian. The public offices in question could be held by women only since the 1940s; men are still the predominant holders of these offices (judges being the exception), which indicates their prevailing male social gender.
Keywords: grammatical gender; leksikalni spol; lexical gender; referenčni spol; referential gender; Slovene-Italian contrastive analysis; slovensko-italijanska kontrastivna analiza; slovnični spol; social gender; socialni spol